Effects of binunga [macaranga tanarius (L.) mull. arg.] crude leaf extract on cancer cells, angiogenesis, early implantation, and embryogenesis - Rodriguez, Anna Melissa H.; Reyes, Mikojie F.; Lim, Nielsen Nicholas S.; Tolentino, Jarel Elgin M.; Colet, Lerrie Ann Ipulan (Philippine Journal of Science)
"Medicinal plants have long been known to contain an abundance of natural bioactive compounds, some of which have been studied for their anti-cancer and anti-angiogenic properties. However, testing the possible side effects of a "drug" candidate is not congruently done in vivo. Hence, the effects of these plant extracts on different biological processes are unknown. This study aims to evaluate the anti-cancer and anti-angiogenic activity of the crude leaf extract of the plant Macaranga tanarius (L.) Mull.Arg. while simultaneously assessing its safety"-title page.